Exchange rate regime classifications and exchange rate variability. Issue 5 (23rd March 2016) - You, Yu; Kim, Yoonbai; Hou, Lei
ABSTRACT: It is well known that the exchange rate regime (ERR) declared to the IMF is often different from the actual regime. Several alternative schemes for de facto regime classification have been developed. In this article, we compare the ability of four popular schemes to track exchange rate variability (ERV). We find that the existing ERR classifications do not match well with the degree of ERV, especially for intermediate regimes. For instance, in the Levy-Yeyati and Sturzenegger (2003) coding, the intermediate regimes exhibit greater ERV than the floaters. On the other hand, for the Reinhart and Rogoff (2004) coding, the fixers show greater variability than some intermediates.